METHOD DEVELOPMENT AND VALIDATION FOR SIMULTANEOUS QUANTIFICATION OF NETUPITANT AND PALONOSETRON IN BULK AND PHARMACEUTICAL DOSAGE FORM AND THEIR FORCED DEGRADATION STUDY BY RP-HPLC - M, MANORANJANI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present paper describes a simple, accurate, and precise reversed-phase high-performance liquid chromatography (HPLC) method for rapid and simultaneous quantification of netupitant (NTP) and palonosetron (PLS) in bulk and pharmaceutical dosage form. Methods: The chromatographic separation was achieved on Luna C18 (250 mm × 4.6 mm, 5 μ). Mobile phase contained a mixture of 0.1% orthophosphoric acid and acetonitrile in the ratio of 60:40 v/v, flow rate 1.0 ml/min, and ultraviolet detection at 222 nm. Results: The proposed method shows a good linearity in the concentration range of 60–900 μg/ml for NTP and 0.1–1.5 μg/ml for PLS under optimized conditions. All the precision and recovery results are in between 98 and 102%. In the entire robustness conditions, percentage of relative standard deviation is <2.0%. Degradation has minimum effect in stress condition and solutions are stable up to 24 h. This method is validated different parameters such as precision, linearity, accuracy, limit of detection, limit of quantification, ruggedness, robustness, and forced degradation study were determined according to the International Conference of Harmonization (ICH) Q2B guidelines. Conclusion: All the parameters of validation were found to be within the acceptance range of ICH guidelines. Since there is no HPLC method reported in the literature for the estimation of NTP and PLS in pharmaceutical dosage forms, there is a need to develop quantitative methods under different conditions to achieve improvement in sensitivity, selectivity, etc. Hence, the author has attempted to develop a validation and forced degradation for simultaneous quantification of NTP and PLS.